The Scope and Secret of Obviousness of Affirmations (Tasdiqāt) According to Mulla Sadra and Descartes - Seyyed Mohammad Davood alavi; علی کرباسی زاده اصفهانی; مهدی دهباشی (حکمت اسرا)
Philosophers' efforts to find a solid foundation for understanding and cognition have led to discovery of knowledge which they term as evident or obvious. What is meant by 'evident' and what its relationship with intuition, clarity and distinction? What are its limits and scope? What is the secret for something to be called 'evident'? These are some questions which this article seeks to deal with from the perspectives of Mulla Sadra and Descartes. Studies reveal that there is an overlapping relationship between clarity and distinction on the one hand and obviousness on the other while it is probably synonymous with intuition. These two philosophers' answer about the extent of affirmative obvious matters has equally confined them to awwaliyāt (lit. initials) and wijdaniyāt (i.e. discovered within ourselves through our conscience). However, when it comes to the secrets of the obviousness of affirmations (tasdiqāt) or assent, Sadra is of the view that the statements' inner and conceptual particularities constitute the criterion and secret of their obviousness while Descartes is of the view that the simplicity of those statements is the reason for their obviousness.